From Data Entry to Intelligence: Artificial Intelligence's Impact on Financial System Workflows - Arjun Reddy Kunduru (International Journal on Orange Technologies, 2023)
Invoice processing and payment activities are crucial financial operations for businesses. Traditionally, these tasks involved manual data entry and validation, which is time-consuming and prone to errors. With recent advances in artificial intelligence (AI), intelligent systems can automate and streamline invoice and payment processing, leading to higher efficiency and cost savings. This paper explores the applications of AI in financial document processing, data extraction, verification, reconciliation, and payment execution. The capabilities of AI methods, including computer vision, natural language processing, and machine learning, are analyzed in the context of digitizing financial workflows. Challenges such as the lack of standardized data, the need for integration with legacy systems, and data security considerations are also discussed. The paper concludes that AI-based tools can enable intelligent invoice management, smart approvals, and automated payment processing to transform financial operations.